Application of Rice Root Endophytic Bacteria in Ciherang Variety Rice (Oryza sativa) Seeds - Lenni Fitri; Yulia Sari Ismail; Putriani Putriani; Warzatullisna Warzatullisna (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Endophytic bacteria are microorganisms that thrive in plant tissue without causing any negative effects to the host plants. The purpose of this study was to apply endophytic bacteria that have the potential to produce IAA hormones as biological agents in rice seeds. This research was conducted by testing IAA hormone using a spectrophotometer, testing HCN production using filter paper, biochemically identification of the isolate, and applicating endophytic bacteria into rice seeds. Endophytic bacteria have different abilities in producing IAA hormone. Based on the results of the study, the highest IAA concentration (57 ppm) was obtained from KSB1 (Potassium Solubilizing Bacteria) isolates and followed by KSB3 isolate with 56 ppm. All the endophytic bacteria isolates were unable to produce HCN. Results of the study showed that KSB1 and KSB3 isolate were able to influence the growth of root length by 5.62 cm and 6.70 respectively as well as the canopy height by 8.56 cm and 8.30 cm respectively. Based on observations of colony morphology, cell morphology and biochemical tests, KSB1 was presumably belong to the genus Staphylococcus. In this study, new information about endophytic bacteria that can increase the growth of Ciherang variety rice can be obtained. This study provides information that the application of environmentally friendly bacteria is important to preserve the environment and agriculture sustainability in Indonesia without reducing the productivity of rice.